Dye Absorbance Spectral Study of Complex ions of Zinc-Alkali Chloride in Methanol-Water System - N. Modi, Ashvin.; Desai, C.M.; Farasram, P.L. (Asian Journal of Chemistry, 2010)
Light absorbance spectral investigation has been studied to observechanges in complex ions formation with changes in methanol-water phase.Effect of increase and decrease of dielectric constant on the formation ofcomplex ions, in lead-alkali nitrate and mercuric-alkali halide systems hasbeen earlier reported. With increase in concentration of methanol, withlower dielectric constant in solvent, the dielectric constant of water-methanolmixture decreases with consequent decreasing dissociation of anionicions of salts and thereby decrease in complex ions formation.